Peramalan Permintaan Pasokan Energi Berdasarkan Intensitas Konsumsi Listrik dan Kapasitas Pembangkit Listrik Terpasang - Abdi Musyafiq, Afrizal; Purwanto, Riyadi (P3M Politeknik Negeri Cilacap, 2021)
This research is an important step in energy planning which is the main in electricity planning in the long-term forecast for the demand and supply of energy supply. A simple model is presented using LEAP (Long Term Alternative Energy Planning System) as a broadcasting tool and Central Java as a case study case for this research. This research discusses future energy needs. Electricity needs in the household, industrial, business, and community sectors are calculated based on data on participation, electricity consumption, installed electricity generation capacity, electrification ratio, and electricity strengthening. The base year of this research is 2020 and 2045 is the final period of this forecast. The results of this study indicate that energy needs in Central Java will increase by an average of 23.44% in 2045 or five times compared to 2020 by taking into account various factors of regional economic growth and electricity demand each year